Pengaruh Likuiditas, Leverage terhadap Profitabilitas dimoderasi Ukuran Perusahaan pada Sub Sektor Perusahaan Pertambangan Batu Bara - Saphiera Arsyida Pusaka; Nurjanti Takarini (Universitas Batanghari Jambi, 2023)
Profitability is a measure of a company's success, the more profit it generates, the more successful the company will be. However, there is a phenomenon that indicates that the profits of coal mining companies have decreased, this can be examined through financial reports where the existing liquidity and leverage show phenomena that are suspected of causing a decrease in company profitability. Both of these components can also be influenced by the size of the company. Therefore, this research was conducted to determine the effect of liquidity and leverage on profitability partially and to find out how company size can partially moderate the effect of liquidity and leverage on company profitability. The population in this study were 24 coal mining sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period with a total sample of 21 companies. The data collection method used purposive sampling and this research method used moderated analysis regression (MRA). The results of this study indicate that liquidity has a negative effect on profitability while leverage has a positive effect on profitability and firm size can partially moderate the effect of liquidity and leverage on profitability.